2007
DOI: 10.1016/j.socscimed.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

There's no place like (a) home: Ontological security among persons with serious mental illness in the United States

Abstract: As the homelessness 'crisis' in the United States enters a third decade, few are as adversely affected as persons with serious mental illness. Despite recent evidence favoring a 'housing first' approach, the dominant 'treatment first' approach persists in which individuals must climb a ladder of program requirements before becoming eligible for an apartment of their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
310
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(347 citation statements)
references
References 54 publications
(61 reference statements)
25
310
0
12
Order By: Relevance
“…Les conséquences de cette victimisation sont d'autant plus importantes que les conditions de vie de ces personnes sont précaires et qu'elles parviennent difficilement à obtenir l'aide dont elles ont besoin (Brassard & Cousineau, 2000). Une fois en logement, elles disent d'ailleurs se sentir beaucoup plus en sécurité que lorsqu'elles étaient en situation d'itinérance (Padgett, 2007).…”
Section: Le « Logement D'abord »unclassified
See 2 more Smart Citations
“…Les conséquences de cette victimisation sont d'autant plus importantes que les conditions de vie de ces personnes sont précaires et qu'elles parviennent difficilement à obtenir l'aide dont elles ont besoin (Brassard & Cousineau, 2000). Une fois en logement, elles disent d'ailleurs se sentir beaucoup plus en sécurité que lorsqu'elles étaient en situation d'itinérance (Padgett, 2007).…”
Section: Le « Logement D'abord »unclassified
“…On peut aussi considérer l'hypothèse selon laquelle des problèmes physiques sont à l'origine de ces hospitalisations. Effectivement, une fois logées, les personnes qui étaient en situation d'itinérance prennent conscience qu'elles sont en mauvaise santé physique (Padgett, 2007). Il est donc plausible que ces problèmes seront traités à la suite de leur arrivée dans un logement.…”
Section: L'utilisation Des Servicesunclassified
See 1 more Smart Citation
“…Acquiring a home of your own is reported both to be of vital importance for persons with mental-health and addiction problems (Andvig et al, 2013;Mezzina et al, 2006;Padgett, 2007) and to have a positive influence on recovery processes (Borg et al 2005). A randomized controlled trial (Patterson et al, 2013) has found that participants in HF programmes reported significantly greater overall quality of life compared with clients in conventional treatment programmes.…”
Section: A Home Of Your Ownmentioning
confidence: 99%
“…The findings show that homeless people are under chronic stress because of their efforts to survive with limited resources. Having the security that they will keep their housing and get support as long as they need it is connected with 'ontological security' (Padgett, 2007). Padgett (2007) suggests that 'housing can provide a fundamental building block for ontological security, thus lending support to a housing first approach ' (p. 1934).…”
Section: A Home Of Your Ownmentioning
confidence: 99%